Sulfide solid-state battery cell and preparation method thereof
By introducing oxide solid electrolytes into sulfide solid state batteries, the instability problem between the interface between sulfide electrolytes and electrodes is solved, high-voltage stability and cyclic stability are improved, and the energy density and large-scale production of sulfur-based all-solid state batteries are promoted.
Patent Information
- Application Number
- CN202411715603.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-08
AI Technical Summary
In sulfide solid state batteries, the instability between the interface between the sulfide electrolyte and the electrode leads to increased side reactions, increased polarization and reduced cycle stability, and the sulfide electrolyte is sensitive to moisture, affecting the preparation environment and cost.
An oxide solid electrolyte with high ionic conductivity, high stability and low Young's modulus is introduced, and an interface layer is placed between the sulfide electrolyte layer and the lithium metal negative electrode layer, and a sulfide solid electrolyte is completely replaced in the composite positive electrode layer.
The side reaction between the sulfide electrolyte layer and the positive/negative electrode interface is effectively suppressed, and the high-voltage stability of the composite positive electrode layer is improved, so that the sulfide solid electrolyte can match the lithium metal negative electrode and various positive electrode materials to achieve high specific energy and high stability all-solid lithium metal batteries.
Smart Images

Figure CN119786707A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and specifically relates to a sulfide solid-state battery cell and a preparation method thereof. Background Art
[0002] Traditional lithium-ion batteries use organic liquid electrolytes, which are subject to the risk of electrolyte volatilization, leakage, decomposition and deactivation, which seriously affects the safety and life of high-energy lithium batteries. Using stable solid electrolytes to replace liquid electrolytes that are easily decomposed and volatilized, developing all-solid-state lithium batteries, and using positive and negative electrode materials with higher specific capacity (such as high-voltage positive electrode materials and metal lithium negative electrodes) can improve battery energy density while enhancing safety.
[0003] Among the many technical routes of solid-state lithium batteries, sulfur-based all-solid-state batteries are currently the only all-solid-state battery system that is expected to achieve large-scale application. However, sulfur-based all-solid-state batteries also face many problems, among which the instability problem at the interface between the sulfide solid electrolyte and the electrode is particularly significant. At the interface between the sulfide solid electrolyte and the positive electrode, due to the poor high-voltage stability of the sulfide electrolyte, the sulfide solid electrolyte and the positive electrode active material will react to generate sulfide oxidation products during the charging process, thereby forming a high-impedance interface layer, which is not conducive to ion transmission. For lithium negative electrode all-solid-state batteries, at the interface between the sulfide solid electrolyte and the negative electrode, on the one hand, there is contact loss at the sulfide electrolyte / lithium metal negative electrode interface, which will expand the local current density and cause dendrite growth; on the other hand, the sulfide electrolyte will spontaneously decompose after contacting the metal lithium to form a loose decomposition product layer, which is not conducive to the rapid conduction of lithium ions at the interface. The accumulation of the decomposition product layer at the interface will lead to increased battery polarization and damage the battery's cycle stability. Therefore, the instability of the interface between sulfide solid electrolytes and electrodes poses a challenge to the use of high-capacity positive and negative electrode materials, hindering the further improvement of the energy density of sulfur-based all-solid-state batteries. In addition, the S atoms in sulfide solid electrolytes are very sensitive to humid air and will produce toxic gas hydrogen sulfide, which places high demands on the preparation environment and high production costs, which is not conducive to the large-scale production of sulfide solid-state batteries.
[0004] At present, the strategies for solving the interface problems between sulfide electrolytes and positive electrodes are relatively limited, mainly coating the positive electrode particles with a protective layer, but the processes are mostly cumbersome. The strategies for solving the interface problems between sulfide electrolytes and negative electrodes (metallic lithium) mainly focus on constructing alloy negative electrodes or intermediate layers. Using alloy negative electrodes (such as lithium-indium alloys) instead of metallic lithium can avoid the continuous decomposition of sulfide solid electrolytes, but because the alloy has a higher potential to metallic lithium, the use of alloy negative electrodes will lose the energy density of the battery. The intermediate layer can avoid direct contact between the sulfide solid electrolyte and metallic lithium, thereby protecting the electrolyte from oxidation, but the constructed intermediate layer is mostly a polymer layer or a rigid film layer, which often has low ionic conductivity and will reduce the ion transport performance of the battery cell.
[0005] Therefore, finding a simple and easy method that can effectively improve the stability of sulfide solid-state battery cells is crucial to the further development of sulfide solid-state batteries. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide a sulfide solid-state battery cell and a preparation method thereof, by introducing an oxide solid electrolyte with high ionic conductivity, high stability and low Young's modulus into the interface layer between the sulfide electrolyte layer and the lithium metal negative electrode layer to avoid direct contact between the sulfide and metallic lithium, and completely replacing the sulfide solid electrolyte in the composite positive electrode layer as an ion-conducting substance, the side reaction at the interface between the sulfide electrolyte layer and the positive / negative electrode is effectively suppressed without reducing the ion transport performance, and at the same time, the high-voltage stability of the composite positive electrode layer is improved, so that the sulfide solid electrolyte can be matched with the lithium metal negative electrode and various positive electrode materials, which is of great significance for realizing a high-specific energy and high-stability all-solid-state lithium metal battery without any electrode modification and can be operated at room temperature.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a sulfide solid-state battery cell, comprising a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer, characterized in that the sulfide solid-state battery cell also includes an oxide solid electrolyte, and the oxide solid electrolyte forms an interface layer between the sulfide solid electrolyte layer and the negative electrode layer, and completely replaces the sulfide solid electrolyte in the composite positive electrode layer.
[0008] Furthermore, the method for preparing the sulfide solid-state battery cell comprises the following steps:
[0009] S1, obtaining a composite positive electrode layer by a method of laminating and hot roller treatment after sufficient mixing, with a pressure of 100-180 MPa and a temperature of 20-50°C;
[0010] S2. A mixture of a sulfide solid electrolyte and a small amount of polymer is subjected to a lamination hot roller treatment to obtain a sulfide solid electrolyte layer, the pressure used being 100-180 MPa and the temperature used being 20-50° C.;
[0011] S3, placing an oxide solid electrolyte on the sulfide solid electrolyte layer obtained in step S2 and performing a lamination hot roller treatment to form an oxide solid electrolyte layer on the sulfide solid electrolyte layer, the pressure used is 100-180 MPa, the temperature used is 20-50° C., and the time used is 0.5-2 h;
[0012] S4, placing the negative electrode layer material on the oxide solid electrolyte layer formed in step S3, and then laminating the composite positive electrode layer obtained in step S1 and the sulfide electrolyte layer treated in step S3, and then performing a press treatment to obtain a sulfide solid-state battery cell. The pressure used in the press treatment is 10-30MPa, the temperature used is 20-30°C, and the time used is 10-30min.
[0013] Preferably, the polymer in step S2 is any one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyvinyl chloride, polyvinyl alcohol, and polyurethane;
[0014] Preferably, the oxide solid electrolyte layer formed in step S3 has a thickness of 1 to 5 μm.
[0015] Preferably, the composite positive electrode layer comprises a positive electrode active material, a conductive agent, an oxide solid electrolyte and a binder, and the mass fraction relationship is 50-90:5-20:0.1-20:0.1-10;
[0016] Preferably, the negative electrode layer is a lithium metal negative electrode, which is metal lithium powder or metal lithium foil.
[0017] Preferably, the positive electrode active material is any one of lithium cobalt oxide, olivine type, nickel cobalt manganese oxide, lithium-rich manganese-based oxide, and spinel oxide; the conductive agent is any one of conductive carbon black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; the binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and polyacrylic acid.
[0018] Preferably, the chemical formula of the oxide solid electrolyte is Li a M b (PO4)2, wherein 0<a≤3, 0<b≤3, and M is any one of Sc, Al, Y, La, Ce, Ga, In, Nd, Sm, Te, Tm, Yb, and Lu;
[0019] Preferably, the oxide solid electrolyte is a sheet-like nanomaterial with a size of 100 to 1000 nm.
[0020] Furthermore, the oxide solid electrolyte Li a M b (PO4)2 is a sodium ion conductor Na a M b (PO4)2 is obtained after ion exchange and lamination crushing, and the specific steps are as follows:
[0021] A1. Combine Na2CO3 and MO x After being mixed evenly with NH4H2PO4 in a certain proportion, calcined at 700-1000℃ for 6-12h, the sodium ion conductor Na a M b (PO4)2;
[0022] A2, the Na obtained in step A1 a M b (PO4)2 is mixed evenly with lithium salt LiTFSI and ionic liquid and placed in a reactor. The concentration of the lithium salt in the ionic liquid is 0.1-0.5 mol / L. a M b The molar ratio of (PO4)2 is 3:1; the reaction kettle is placed in a homogeneous reactor, and the reaction kettle is rotated and stirred at a speed of 50 rpm / min for 72-144 hours at a temperature of 100-200°C;
[0023] A3, taking out the product in the reactor described in step A2, centrifuging and separating, drying, and calcining at 400-500°C to obtain micron-sized Li a M b (PO4)2;
[0024] A4, the micron-sized Li a M b The (PO4)2 powder was placed in a ball mill and milled at a speed of 100-400 rpm / min for 1-2 hours before being taken out;
[0025] A5. Laminating the powder obtained in step A4, crushing the powder under a pressure of 10-30 MPa for 2-4 hours, putting the powder into a ball mill, and milling the powder at a speed of 100-400 rpm / min for 1-2 hours before taking it out;
[0026] A6. Repeat steps A4 to A5 three times to obtain nanoscale Li a M b (PO4)2 powder.
[0027] Preferably, the ionic liquid in step A2 is any one of imidazole ionic liquids, quaternary ammonium ionic liquids, piperidine ionic liquids, and pyrrole ionic liquids.
[0028] Preferably, the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0029] Preferably, the sulfide electrolyte is Li 10 GeP2S 12 Type, Thio-LiSICON, Argentum-like Li 7-a+b P 1- b M b S 6-a-c N c X a , any one of the compounds (100-x) Li2S-xP2S5, wherein M=Si, Ge, Sn, N=Se, Te, X=Cl, Br, I, a=0~2, b=0~1, c=0~1, 10≤x≤50.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] (1) The oxide solid electrolyte Li used in the present invention a M b (PO4)2 has both the high stability of oxide solid electrolytes (including air stability and electrochemical stability) and the low Young's modulus and high ionic conductivity of sulfide solid electrolytes. Placing it between the sulfide solid electrolyte layer and the lithium metal negative electrode layer can effectively prevent the sulfide electrolyte from being reduced by metallic lithium at the interface. At the same time, its fast ion transport characteristics can prevent the ion transport inside the sulfide solid battery cell from being affected. Therefore, the use of lithium metal negative electrodes in sulfide solid battery cells can be realized, which helps to improve the energy density of the battery.
[0032] (2) The oxide solid electrolyte Li used in the present invention a M b (PO4)2 has good oxidation resistance and air stability. It is added to the composite positive electrode layer as an ion-conducting material to replace the sulfide solid electrolyte in the composite positive electrode of the traditional sulfide solid battery cell. On the one hand, it is beneficial to improve the oxidation resistance of the composite positive electrode layer, so that the use of high-voltage positive electrode materials in sulfide solid battery cells can be realized, while improving the cycle stability; on the other hand, the use of air-stable Li a M b (PO4)2 is beneficial to simplifying the preparation environment of the composite positive electrode layer, thereby reducing the preparation cost.
[0033] (3) The oxide solid electrolyte Li used in the present inventiona M b (PO4)2 is a sodium ion conductor Na a M b (PO4)2 is obtained by ion exchange and lamination crushing. During the ion exchange process, Na a M b The Na with the larger ionic radius in (PO4)2 + The smaller ionic radius of Li + Replacement, Li a M b The (PO4)2 crystal structure changes, including lattice distortion caused by structural contraction and changes in crystal orientation. a M b There are cracks in the (PO4)2 particles along a certain orientation. After multiple lamination and crushing, the crystal plane where the cracks are generated can be fully exposed, making the micron-sized Li a M b The (PO4)2 particles split along the cracks and eventually formed a flake-like Li a M b (PO4)2 nanosheets. Similar to two-dimensional materials such as boron nitride nanosheets and graphene, Li a M b (PO4)2 nanosheets have a unique stacking effect and are easy to form thin films during the sheeting process. Therefore, in the preparation process of sulfide solid-state battery cells, the thickness of the oxide solid electrolyte layer formed on the sulfide solid electrolyte layer by laminating hot rollers can be less than 5μm, which can avoid affecting the volume energy density and mass energy density of the battery cell. At the same time, as an intermediate layer, it is also conducive to the transmission of ions between the electrolyte layer and the metal lithium negative electrode.
[0034] (4) The oxide solid electrolyte Li used in the present invention a M b (PO4)2 has the characteristic of low Young's modulus, which is beneficial to provide good interface contact and reduce polarization inside the battery cell compared to the high rigidity of traditional oxide solid electrolytes.
[0035] (5) The preparation method of the sulfide solid-state battery cell provided by the present invention has a simple process and is conducive to reducing production costs, which is of great significance for realizing large-scale production of sulfide solid-state battery cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solution disclosed in the present invention, the drawings required to be used in some embodiments disclosed in the present invention are briefly introduced below. Obviously, the drawings in the following description are only drawings of some embodiments disclosed in the present invention and do not constitute a limitation to the technical solution disclosed in the present invention.
[0037] Figure 1 A schematic diagram of the structure of a sulfide solid-state battery cell provided by the present invention;
[0038] Figure 2 This is a scanning electron microscope (SEM) morphology image of the oxide solid electrolyte prepared in Example 1;
[0039] Figure 3 This is an interface morphology diagram of the solid-state battery cell prepared in Example 1;
[0040] Figure 4 This is a comparison diagram of the impedance of the solid-state battery cells prepared in Example 1 and Comparative Example 1;
[0041] Figure 5 This is the constant current charge and discharge curve of the lithium / oxide solid electrolyte layer-sulfide electrolyte layer-oxide solid electrolyte layer / lithium symmetric battery prepared in Example 2. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0043] The present invention provides a sulfide solid-state battery cell, comprising a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer, characterized in that the sulfide solid-state battery cell also includes an oxide solid electrolyte, and the oxide solid electrolyte forms an interface layer between the sulfide solid electrolyte layer and the negative electrode layer, and completely replaces the sulfide solid electrolyte in the composite positive electrode layer.
[0044] Furthermore, the method for preparing the sulfide solid-state battery cell comprises the following steps:
[0045] S1, obtaining a composite positive electrode layer by a method of laminating and hot roller treatment after sufficient mixing, with a pressure of 100-180 MPa and a temperature of 20-50°C;
[0046] S2. A mixture of a sulfide solid electrolyte and a small amount of polymer is subjected to a lamination hot roller treatment to obtain a sulfide solid electrolyte layer, the pressure used being 100-180 MPa and the temperature used being 20-50° C.;
[0047] S3, placing an oxide solid electrolyte on the sulfide solid electrolyte layer obtained in step S2 and performing a lamination hot roller treatment to form an oxide solid electrolyte layer on the sulfide solid electrolyte layer, the pressure used is 100-180 MPa, the temperature used is 20-50° C., and the time used is 0.5-2 h;
[0048] S4, placing the negative electrode layer material on the oxide solid electrolyte layer formed in step S3, and then laminating the composite positive electrode layer obtained in step S1 and the sulfide electrolyte layer treated in step S3, and then performing a press treatment to obtain a sulfide solid-state battery cell. The pressure used in the press treatment is 10-30MPa, the temperature used is 20-30°C, and the time used is 10-30min.
[0049] Preferably, the polymer in step S2 is any one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyvinyl chloride, polyvinyl alcohol, and polyurethane;
[0050] Preferably, the thickness of the oxide solid electrolyte layer formed in step S3 is 1-5 μm.
[0051] Preferably, the composite positive electrode layer comprises a positive electrode active material, a conductive agent, an oxide solid electrolyte and a binder, and the mass fraction relationship is 50-90:5-20:0.1-20:0.1-10;
[0052] Preferably, the negative electrode layer is a lithium metal negative electrode, which is metal lithium powder or metal lithium foil.
[0053] Preferably, the positive electrode active material is any one of lithium cobalt oxide, olivine type, nickel cobalt manganese oxide, lithium-rich manganese-based oxide, and spinel oxide; the conductive agent is any one of conductive carbon black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; the binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and polyacrylic acid.
[0054] Preferably, the chemical formula of the oxide solid electrolyte is Li a M b (PO4)2, wherein 0<a≤3, 0<b≤3, and M is any one of Sc, Al, Y, La, Ce, Ga, In, Nd, Sm, Te, Tm, Yb, and Lu;
[0055] Preferably, the oxide solid electrolyte is a sheet-like nanomaterial with a size of 100 to 1000 nm.
[0056] Furthermore, the oxide solid electrolyte Li a M b(PO4)2 is a sodium ion conductor Na a M b (PO4)2 is obtained after ion exchange and lamination crushing, and the specific steps are as follows:
[0057] A1. Combine Na2CO3 and MO x After being mixed evenly with NH4H2PO4 in a certain proportion, calcined at 700-1000℃ for 6-12h, the sodium ion conductor Na a M b (PO4)2;
[0058] A2, the Na obtained in step A1 a M b (PO4)2 is mixed evenly with lithium salt LiTFSI and ionic liquid and placed in a reactor. The concentration of the lithium salt in the ionic liquid is 0.1-0.5 mol / L. a M b The molar ratio of (PO4)2 is 3:1; the reaction kettle is placed in a homogeneous reactor, and the reaction kettle is rotated and stirred at a speed of 50 rpm / min for 72-144 hours at a temperature of 100-200°C;
[0059] A3, taking out the product in the reactor described in step A2, centrifuging and separating, drying, and calcining at 400-500°C to obtain micron-sized Li a M b (PO4)2;
[0060] A4, the micron-sized Li a M b The (PO4)2 powder was placed in a ball mill and milled at a speed of 100-400 rpm / min for 1-2 hours before being taken out;
[0061] A5. Laminating the powder obtained in step A4, crushing the powder under a pressure of 10-30 MPa for 2-4 hours, putting the powder into a ball mill, and milling the powder at a speed of 100-400 rpm / min for 1-2 hours before taking it out;
[0062] A6. Repeat steps A4 to A5 three times to obtain nanoscale Li a M b (PO4)2 powder.
[0063] Preferably, the ionic liquid in step A2 is any one of imidazole ionic liquids, quaternary ammonium ionic liquids, piperidine ionic liquids, and pyrrole ionic liquids.
[0064] Preferably, the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0065] Preferably, the sulfide electrolyte is Li 10 GeP2S 12 Type, Thio-LiSICON, Argentum-like Li 7-a+b P 1- b M b S 6-a-c N c X a , any one of the compounds (100-x) Li2S-xP2S5, wherein M=Si, Ge, Sn, N=Se, Te, X=Cl, Br, I, a=0~2, b=0~1, c=0~1, 10≤x≤50.
[0066] Based on this, the structural schematic diagram of a sulfide solid-state battery cell provided by the present invention is as follows Figure 1 As shown, it includes a composite positive electrode layer a, a sulfide electrolyte layer b, an oxide electrolyte layer c and a negative electrode layer d. In addition, the solid-state battery cell may also include other components such as a current collector, a tab and a packaging film, and the current collector, the tab and the packaging film are components commonly used in the art.
[0067] Embodiment 1:
[0068] The present embodiment provides a sulfide solid-state battery cell, comprising a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer. The sulfide solid-state battery cell also includes an oxide solid electrolyte. The oxide solid electrolyte forms an interface layer between the sulfide solid electrolyte layer and the negative electrode layer, and completely replaces the sulfide solid electrolyte in the composite positive electrode layer.
[0069] The composite positive electrode layer includes a positive electrode active material, lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM811), conductive agent SuperP, oxide solid electrolyte Li3La(PO4)2 and binder polyvinylidene fluoride (PVDF), the mass ratio is 50:30:10:10;
[0070] The negative electrode layer is a lithium metal negative electrode, which is a metal lithium foil pressed from a metal lithium ribbon.
[0071] The sulfide electrolyte is Li6PS5Cl.
[0072] The oxide solid electrolyte is Li3La(PO4)2 nanosheets, which are obtained by ion exchange, lamination and crushing of the sodium ion conductor Na3La(PO4)2. The specific steps are as follows:
[0073] 1) Na2CO3, La2O3 and NH4H2PO4 were mixed evenly in a stoichiometric molar ratio of 3:1:4, and calcined at 1000°C for 10 hours to obtain a sodium ion conductor Na3La(PO4)2;
[0074] 2) preparing a 0.5 mol / L ionic liquid solution of lithium salt LiTFSI, wherein the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, uniformly mixing the Na3La(PO4)2 obtained in step (1) with the LiTFSI ionic liquid solution, and placing the mixture in a reactor, wherein the concentration of the lithium salt in the ionic liquid is 0.1-0.5 mol / L, and the molar ratio of LiTFSI to Na3La(PO4)2 is 3:1; placing the reactor in a homogeneous reactor, rotating and stirring at a speed of 50 rpm / min for 72 h, and the temperature is 120°C;
[0075] 3) taking out the product in the reaction kettle of step (2), separating it by centrifugation, drying it, and calcining it at 450° C. to obtain micron-sized Li3La(PO4)2;
[0076] 4) placing the micron-sized Li3La(PO4)2 powder obtained in step (3) into a ball mill, milling at a speed of 100 rpm / min for 2 h, and then taking it out;
[0077] 5) The powder obtained in step (4) was subjected to lamination treatment, and the powder was crushed after being subjected to a pressure treatment of 30 MPa for 2 h, and then put into a ball mill, and ball milled at a speed of 100 rpm / min for 2 h before being taken out;
[0078] 6) After repeating steps (4) to (5) three times, nanoscale Li3La(PO4)2 powder is obtained.
[0079] Based on the above preparation method, the scanning electron microscope (SEM) morphology of the oxide solid electrolyte prepared in Example 1 is as follows Figure 2 As shown in the figure, it can be seen that the final Li3La(PO4)2 powder presents a nanosheet morphology with a size between 500nm and 1μm. Li3La(PO4)2 nanosheets have a unique stacking effect and are easy to form a thin film during the tableting process, which is also the reason why its Young's modulus is low and easy to press.
[0080] The preparation method of the sulfide solid-state battery cell comprises the following steps:
[0081] 1) The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1O2, NCM811), conductive agent SuperP, oxide solid electrolyte Li3La(PO4)2, and binder polyvinylidene fluoride (PVDF) are fully mixed in a mass ratio of 50:30:10:10, and then a composite positive electrode layer is obtained by laminating hot rollers at a pressure of 120 MPa;
[0082] 2) After mixing the sulfide solid electrolyte Li6PS5Cl and PVDF in a mass ratio of 95:5, a sulfide solid electrolyte layer was prepared by laminating with a hot roller at a temperature of 45°C and a pressure of 180 MPa;
[0083] 3) Laying the oxide solid electrolyte Li3La(PO4)2 on the sulfide solid electrolyte layer obtained in step (2) and performing a lamination hot roller treatment to form an oxide solid electrolyte layer on the sulfide solid electrolyte layer, the pressure used is 120 MPa, the temperature used is 45°C, and the time used is 1 hour;
[0084] 4) After placing the metal lithium strip on the oxide solid electrolyte layer formed in step (3), the composite positive electrode layer obtained in step (1) and the sulfide electrolyte layer treated in step (3) are laminated, and then pressed together at room temperature to obtain a sulfide solid-state battery cell. The pressure used during the pressing treatment is 30 MPa and the time used is 30 min.
[0085] Based on the above preparation method, the interface morphology of the solid-state battery cell prepared in Example 1 is as follows: Figure 3 As shown in the figure, it can be seen that the thickness of the oxide solid electrolyte layer in this embodiment 1 is about 5μm and the morphology is dense; the oxide solid electrolyte layer is located between the sulfide solid electrolyte layer and the lithium metal negative electrode layer, and the three are in close contact, which can significantly reduce the battery impedance.
[0086] Comparative Example 1:
[0087] This comparative example provides a sulfide solid-state battery cell, including a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer. The difference from the sulfide solid-state battery cell described in Example 1 is that the sulfide solid-state battery cell described in this comparative example does not contain an oxide solid electrolyte, and the composite positive electrode layer includes a positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM811), conductive agent SuperP, sulfide solid electrolyte Li6PS5Cl and binder polyvinylidene fluoride (PVDF), with a mass ratio of 50:30:10:10.
[0088] The preparation method of the sulfide solid-state battery cell comprises the following steps:
[0089] 1) The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM811), conductive agent SuperP, sulfide solid electrolyte Li6PS5Cl, and binder polyvinylidene fluoride (PVDF) are fully mixed in a mass ratio of 50:30:10:10, and then a composite positive electrode layer is obtained by laminating hot rollers at a pressure of 120 MPa;
[0090] 2) After mixing the sulfide solid electrolyte Li6PS5Cl and PVDF in a mass ratio of 95:5, a sulfide solid electrolyte layer was prepared by laminating with a hot roller at a temperature of 45°C and a pressure of 180 MPa;
[0091] 3) After placing the metal lithium strip on the sulfide solid electrolyte layer formed in step (2), the composite positive electrode layer obtained in step (1) is laminated to the sulfide electrolyte layer, and then a press treatment is performed at room temperature to obtain a sulfide solid-state battery cell. The pressure used in the press treatment is 30 MPa and the time used is 30 min.
[0092] The impedance comparison diagram of the solid-state battery cells prepared in Example 1 (B) and Comparative Example 1 (A) is as follows: Figure 4 As shown in the figure, it can be seen that after the optimization design according to the technical solution of the present invention, the components are in close contact, the initial impedance of the battery is reduced from 161Ω to 56Ω, and the interface impedance is greatly reduced, indicating that the oxide solid electrolyte layer introduced by the present invention shows high stability for high nickel positive electrode, metal lithium negative electrode and sulfide solid electrolyte, which can effectively avoid the side reaction at the interface between sulfide solid electrolyte and positive and negative electrodes in sulfide solid battery, which is beneficial to improve the cycle stability of the battery.
[0093] Embodiment 2:
[0094] The present embodiment provides a sulfide solid-state battery cell, comprising a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer. The sulfide solid-state battery cell also includes an oxide solid electrolyte. The oxide solid electrolyte forms an interface layer between the sulfide solid electrolyte layer and the negative electrode layer, and completely replaces the sulfide solid electrolyte in the composite positive electrode layer.
[0095] The composite positive electrode layer includes positive electrode active material lithium-rich manganese-based oxide (Li-NCM811), conductive agent SuperP, oxide solid electrolyte Li3La(PO4)2 and binder polyvinylidene fluoride (PVDF), with a mass ratio of 45:35:10:10.
[0096] The negative electrode layer is a lithium metal negative electrode, which is a metal lithium foil pressed from a metal lithium ribbon.
[0097] The sulfide electrolyte is Li 10 GeP2S 12 .
[0098] The oxide solid electrolyte is Li3La(PO4)2 nanosheets, which are obtained by ion exchange, lamination and crushing of the sodium ion conductor Na3La(PO4)2. The specific steps are as follows:
[0099] 1) Na2CO3, La2O3 and NH4H2PO4 were mixed evenly in a stoichiometric molar ratio of 3:1:4, and calcined at 1000°C for 10 hours to obtain a sodium ion conductor Na3La(PO4)2;
[0100] 2) preparing a 0.5 mol / L ionic liquid solution of lithium salt LiTFSI, wherein the ionic liquid is 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt, uniformly mixing Na3La(PO4)2 and the LiTFSI ionic liquid solution, and placing the mixture in a reactor, wherein the concentration of the lithium salt in the ionic liquid is 0.1-0.5 mol / L, and the molar ratio of LiTFSI to Na3La(PO4)2 is 3:1; placing the reactor in a homogeneous reactor, rotating and stirring at a speed of 50 rpm / min for 72 h, and the temperature is 120°C;
[0101] 3) taking out the product in the reaction kettle of step (2), separating it by centrifugation, drying it, and calcining it at 450° C. to obtain micron-sized Li3La(PO4)2;
[0102] 4) placing the micron-sized Li3La(PO4)2 powder obtained in step (3) into a ball mill, milling at a speed of 100 rpm / min for 2 h, and then taking it out;
[0103] 5) The powder obtained in step (4) was subjected to lamination treatment, and the powder was crushed after being subjected to a pressure treatment of 30 MPa for 2 h, and then put into a ball mill, and ball milled at a speed of 100 rpm / min for 2 h before being taken out;
[0104] 6) After repeating steps (4) to (5) three times, nanoscale Li3La(PO4)2 powder is obtained.
[0105] The preparation method of the sulfide solid-state battery cell comprises the following steps:
[0106] 1) The positive electrode active material lithium-rich manganese-based oxide (Li-NCM811), the conductive agent SuperP, the oxide solid electrolyte Li3La(PO4)2, and the binder polyvinylidene fluoride (PVDF) were fully mixed in a mass ratio of 45:35:10:10, and then a composite positive electrode layer was obtained by laminating with a hot roller at a pressure of 120 MPa;
[0107] 2) Sulfide solid electrolyte Li 10 GeP2S 12 After being mixed with PVDF in a mass ratio of 95:5, a sulfide solid electrolyte layer was prepared by laminating hot rollers at a temperature of 45°C and a pressure of 180MPa;
[0108] 3) Laying the oxide solid electrolyte Li3La(PO4)2 on the sulfide solid electrolyte layer obtained in step (2) and performing a lamination hot roller treatment to form an oxide solid electrolyte layer on the sulfide solid electrolyte layer, the pressure used is 120 MPa, the temperature used is 45°C, and the time used is 1 hour;
[0109] 4) After placing the metal lithium strip on the oxide solid electrolyte layer formed in step (3), the composite positive electrode layer obtained in step (1) and the sulfide electrolyte layer treated in step (3) are laminated, and then pressed together at room temperature to obtain a sulfide solid-state battery cell. The pressure used during the pressing treatment is 30 MPa and the time used is 30 min.
[0110] In order to verify the improvement effect of the oxide solid electrolyte layer on the sulfide solid electrolyte / lithium interface stability, the present invention prepared a lithium / oxide solid electrolyte layer-sulfide electrolyte layer-oxide solid electrolyte layer / lithium symmetric battery. The constant current charge and discharge curve of the lithium symmetric battery prepared in Example 2 is as follows: Figure 5 As shown, the current density is 0.2 mA cm -2 Each charge or discharge time is 0.5 hours. Figure 5 It can be seen that the symmetrical battery can be stably cycled for more than 800 hours, the voltage platform is flat without obvious fluctuations, and the overpotential is stable at around ±50 mV, which further verifies the long-cycle stability of the solid-state battery cell provided by the present invention.
[0111] Embodiment 3:
[0112] The present embodiment provides a sulfide solid-state battery cell, comprising a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer. The sulfide solid-state battery cell also includes an oxide solid electrolyte. The oxide solid electrolyte forms an interface layer between the sulfide solid electrolyte layer and the negative electrode layer, and completely replaces the sulfide solid electrolyte in the composite positive electrode layer.
[0113] The composite positive electrode layer includes positive electrode active material lithium cobalt oxide (LiCoO2, LCO), conductive agent graphene, oxide solid electrolyte Li3Ce(PO4)2 and binder polytetrafluoroethylene (PTFE), with a mass ratio of 50:30:10:10.
[0114] The negative electrode layer is a lithium metal negative electrode, which is a metal lithium foil pressed from a metal lithium ribbon.
[0115] The sulfide electrolyte is Li 10 GeP2S 12 .
[0116] The oxide solid electrolyte is Li3Ce(PO4)2 nanosheets, which are obtained by ion exchange, lamination and crushing of the sodium ion conductor Na3Ce(PO4)2. The specific steps are as follows:
[0117] 1) Na2CO3, CeO2 and NH4H2PO4 were mixed evenly in a stoichiometric molar ratio of 3:1:4, and calcined at 800°C for 6h to obtain a sodium ion conductor Na3Ce(PO4)2;
[0118] 2) preparing a 0.5 mol / L ionic liquid solution of lithium salt LiTFSI, wherein the ionic liquid is 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt, uniformly mixing Na3Ce(PO4)2 and the LiTFSI ionic liquid solution, and placing the mixture in a reactor, wherein the concentration of the lithium salt in the ionic liquid is 0.1-0.5 mol / L, and the molar ratio of LiTFSI to Na3Ce(PO4)2 is 3:1; placing the reactor in a homogeneous reactor, rotating and stirring at a speed of 50 rpm / min for 72 h, and the temperature is 180°C;
[0119] 3) taking out the product in the reaction kettle of step (2), separating it by centrifugation, drying it, and calcining it at 450° C. to obtain micron-sized Li3Ce(PO4)2;
[0120] 4) placing the micron-sized Li3La(PO4)2 powder obtained in step (3) into a ball mill, milling at a speed of 100 rpm / min for 2 h, and then taking it out;
[0121] 5) The powder obtained in step (4) was subjected to lamination treatment, and the powder was crushed after being subjected to a pressure treatment of 30 MPa for 2 h, and then put into a ball mill, and ball milled at a speed of 100 rpm / min for 2 h before being taken out;
[0122] 6) After repeating steps (4) to (5) three times, nanoscale Li3Ce(PO4)2 powder is obtained.
[0123] The preparation method of the sulfide solid-state battery cell comprises the following steps:
[0124] 1) The positive electrode active material lithium cobalt oxide (LiCoO2, LCO), the conductive agent graphene, the oxide solid electrolyte Li3Ce(PO4)2, and the binder polytetrafluoroethylene (PTFE) are fully mixed in a mass ratio of 50:30:10:10, and then a composite positive electrode layer is obtained by laminating with a hot roller at a pressure of 120 MPa;
[0125] 2) Sulfide solid electrolyte Li 10 GeP2S 12 After being mixed with PTFE in a mass ratio of 96:4, a sulfide solid electrolyte layer was prepared by laminating with a hot roller at a temperature of 45°C and a pressure of 180MPa;
[0126] 3) Laying the oxide solid electrolyte Li3Ce(PO4)2 on the sulfide solid electrolyte layer obtained in step (2) and performing a lamination hot roller treatment to form an oxide solid electrolyte layer on the sulfide solid electrolyte layer, the pressure used is 120 MPa, the temperature used is 45°C, and the time used is 1 hour;
[0127] 4) After placing the metal lithium strip on the oxide solid electrolyte layer formed in step (3), the composite positive electrode layer obtained in step (1) and the sulfide electrolyte layer treated in step (3) are laminated, and then pressed together at room temperature to obtain a sulfide solid-state battery cell. The pressure used in the pressing treatment is 20 MPa and the time used is 30 minutes.
[0128] The results of the above embodiments show that the technical solution provided by the present invention significantly improves the performance of the sulfide solid-state battery cell. By adding an oxide electrolyte layer (high ionic conductivity, oxidation resistance, low Young's modulus, high air stability) with a unique structure and performance between the sulfide electrolyte layer and the metal lithium negative electrode layer, the spontaneous decomposition reaction after the sulfide electrolyte is directly in contact with the metal lithium is avoided, so that the use of the metal lithium negative electrode in the sulfide solid-state battery becomes possible, which is conducive to the further improvement of the battery energy density. At the same time, the sulfide electrolyte is replaced by an oxide electrolyte as an ion-conducting substance in the composite positive electrode layer, which avoids the high impedance interface layer generated due to the poor oxidation resistance of the sulfide electrolyte, and improves the high-voltage stability of the composite positive electrode. In addition, the oxide electrolyte layer is formed by pressing a single powder material, and the preparation method process is simple. The original solid-state battery cell manufacturing process does not increase the cumbersome preparation process. At the same time, the use of a part of the sulfide material is reduced in the entire cell preparation process, and it is replaced by an air-stable oxide material, which is conducive to simplifying the preparation environment, reducing the production cost to a certain extent, and realizing the large-scale production of sulfide solid-state battery cells is of great significance.
[0129] Although the contents of the present invention have been described in detail through the above-mentioned preferred embodiments, it should be recognized that the above description should not be regarded as limiting the present invention, and any technical personnel in this field can make possible changes and modifications to the technical solution of the present invention by using the above-mentioned disclosed contents without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the contents of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A sulfide solid-state battery cell, comprising a composite positive electrode layer, a sulfide solid electrolyte layer and a negative electrode layer, characterized in that: The sulfide solid-state battery cell also includes an oxide solid-state electrolyte, which forms an interface layer between the sulfide solid-state electrolyte layer and the negative electrode layer, and completely replaces the sulfide solid-state electrolyte in the composite positive electrode layer.
2. The sulfide solid-state battery cell according to claim 1, characterized in that: The preparation method of the sulfide solid-state battery cell comprises the following steps: S1, obtaining a composite positive electrode layer by a method of laminating and hot roller treatment after sufficient mixing, with a pressure of 100-180 MPa and a temperature of 20-50°C; S2. A mixture of a sulfide solid electrolyte and a small amount of polymer is subjected to a lamination hot roller treatment to obtain a sulfide solid electrolyte layer, the pressure used being 100-180 MPa and the temperature used being 20-50° C.; S3, placing an oxide solid electrolyte on the sulfide solid electrolyte layer obtained in step S2 and performing a lamination hot roller treatment to form an oxide solid electrolyte layer on the sulfide solid electrolyte layer, the pressure used is 100-180 MPa, the temperature used is 20-50° C., and the time used is 0.5-2 h; S4, placing the negative electrode layer material on the oxide solid electrolyte layer formed in step S3, and then laminating the composite positive electrode layer obtained in step S1 and the sulfide electrolyte layer treated in step S3, and then performing a press treatment to obtain a sulfide solid-state battery cell. The pressure used in the press treatment is 10-30MPa, the temperature used is 20-30°C, and the time used is 10-30min.
3. The sulfide solid-state battery cell according to claim 2, characterized in that: The polymer in step S2 is any one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyvinyl chloride, polyvinyl alcohol, and polyurethane; The thickness of the oxide solid electrolyte layer formed in step S3 is 1 to 5 μm.
4. The sulfide solid-state battery cell according to claim 1 or 2, characterized in that: The composite positive electrode layer includes a positive electrode active material, a conductive agent, an oxide solid electrolyte and a binder, and the mass fraction relationship is 50-90:5-20:0.1-20:0.1-10; The negative electrode layer is a lithium metal negative electrode, which is metal lithium powder or metal lithium foil.
5. The sulfide solid-state battery cell according to claim 4, characterized in that: The positive electrode active material is any one of lithium cobalt oxide, olivine type, nickel cobalt manganese oxide, lithium-rich manganese-based oxide, and spinel oxide; the conductive agent is any one of conductive carbon black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; the binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and polyacrylic acid.
6. The sulfide solid-state battery cell according to claim 1 or 2, characterized in that: The chemical formula of the oxide solid electrolyte is Li a M b (PO4)2, wherein 0<a≤3, 0<b≤3, and M is any one of Sc, Al, Y, La, Ce, Ga, In, Nd, Sm, Te, Tm, Yb, and Lu; The oxide solid electrolyte is a sheet-like nano material with a size of 100 to 1000 nm.
7. The sulfide solid-state battery cell according to claim 6, characterized in that: The oxide solid electrolyte Li a M b (PO4)2 is a sodium ion conductor Na a M b (PO4)2 is obtained after ion exchange and lamination crushing, and the specific steps are as follows: A1. Combine Na2CO3 and MO x After being mixed evenly with NH4H2PO4 in a certain proportion, calcined at 700-1000℃ for 6-12h, the sodium ion conductor Na a M b (PO4)2; A2, the Na obtained in step A1 a M b (PO4)2 is mixed evenly with lithium salt LiTFSI and ionic liquid and placed in a reactor. The concentration of the lithium salt in the ionic liquid is 0.1-0.5 mol / L. a M b The molar ratio of (PO4)2 is 3:1; the reaction kettle is placed in a homogeneous reactor, and the reaction kettle is rotated and stirred at a speed of 50 rpm / min for 72-144 hours at a temperature of 100-200°C; A3, taking out the product in the reactor described in step A2, centrifuging and separating, drying, and calcining at 400-500°C to obtain micron-sized Li a M b (PO4)2; A4, the micron-sized Li a M b The (PO4)2 powder was placed in a ball mill and milled at a speed of 100-400 rpm / min for 1-2 hours before being taken out; A5. Laminating the powder obtained in step A4, crushing the powder under a pressure of 10-30 MPa for 2-4 hours, putting the powder into a ball mill, and milling the powder at a speed of 100-400 rpm / min for 1-2 hours before taking it out; A6. Repeat steps A4 to A5 three times to obtain nanoscale Li a M b (PO4)2 powder.
8. The sulfide solid-state battery cell according to claim 7, characterized in that: The ionic liquid in step A2 is any one of imidazole ionic liquids, quaternary ammonium ionic liquids, piperidine ionic liquids, and pyrrole ionic liquids.
9. The sulfide solid-state battery cell according to claim 8, characterized in that: The ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
10. The sulfide solid-state battery cell according to claim 1 or 2, characterized in that: The sulfide electrolyte is Li 10 GeP2S 12 Type, Thio-LiSICON, Argentum-like Li 7-a+b P 1-b M b S 6-a-c N c X a , any one of the compounds (100-x) Li2S-xP2S5, wherein M=Si, Ge, Sn, N=Se, Te, X=Cl, Br, I, a=0~2, b=0~1, c=0~1, 10≤x≤50.